Programa de fisioterapia preventiva via aplicativo móvel para trabalhadores: um ensaio clinico randomizado - Bombarda, Larissa Tumelero (2025)
Preventive physiotherapy plays a central role in health promotion, especially through strategies that include health education and specific occupational disease prevention programs. This study aimed to investigate the effects of a preventive physiotherapy protocol mediated by a mobile application on workers' health, focusing on self-perception of health and assessment of thoracolumbar flexibility. To this end, the results obtained before and after the intervention were compared. This is a randomized controlled clinical trial, with a quantitative-qualitative approach, which evaluated the effectiveness of a remote intervention carried out through the WhatsApp application. The intervention lasted 12 weeks, during which participants received educational content in different audiovisual formats, providing guidance on practices for preventing musculoskeletal diseases and encouraging the adoption of healthy habits. The intervention addressed fundamental aspects such as the importance of adherence to preventive physiotherapy, physical ergonomics applied to spinal health, the negative impacts of bad postures during the workday, and the harm caused by physical inactivity in the workplace. The guidelines were sent weekly through short videos, short audios and explanatory images. From the second week onwards, participants were encouraged to complete tasks related to the topic covered in the previous week, with the aim of fostering knowledge about self-care for health. The activities promoted included physical exercises, postural guidance and recommendations for adopting healthy habits, reinforcing the importance of preventive physiotherapy for the quality of life of workers. The study included 19 workers from a higher education institution located in the interior of Rio Grande do Sul, who were divided into two groups: control and intervention. The control group received no intervention, while the intervention group participated in the activities offered through the application. All participants were assessed at two times - before and after the intervention period - in relation to self-perception of health and thoracolumbar flexibility. Quantitative and qualitative questionnaires and analysis of thoracolumbar flexibility measurements were used for the assessment. The results indicated that the technology-mediated preventive physiotherapy protocol did not promote statistically significant improvements in the participants' perception of preventive practice, nor in thoracolumbar flexibility. Despite this, these findings do not invalidate the proposal, but rather highlight the need for reformulations in the adopted protocol, as well as the incorporation of complementary approaches that enhance its effects. Furthermore, the research demonstrated the feasibility of implementing this type of intervention in the workplace, serving as a basis for future investigations aimed at methodological improvement and expanding the positive impacts on the health and well-being of workers.